Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 9 - Cumulative Review: 36

Answer

a. $48x^{2a}$ b. $y^{10b+3}$

Work Step by Step

a. $3x^{4a}(4x^{-a})^2$ $=3x^{4a}(4^2x^{-2a})$ $=(3)(4^2)(x^{4a-2a})$ $=(48)(x^{2a})$ $=48x^{2a}$ b. $\frac{(y^{4b})^3}{y^{2b-3}}$ $=\frac{y^{12b}}{y^{2b-3}}$ $=y^{12b-(2b-3)}$ $=y^{10b+3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.